Ch. 249, Subchapter 7-Crimes against Public Health and Safety, §283 in 1909, Wash. Sess. Laws 965, 977-78 (1909 E. L. Boardman). - (:unkn) unknown (My University, 1909)
Every proprietor, lessee or occupant of any place of amusement, or any plat of ground or building, who shall allow it to be* used for the exhibition of skill in throwing any sharp instrument or in shooting any bow gun, pistol or firearm of any description, at or toward any human being, shall be guilty of a misdemeanor.
Keywords: DISCHARGE